Fragmentation of Islamic Knowledge in the Social Media Era: The Impact of Piecemeal Islamic Preaching Content on the Community's Understanding - rolando, dede (UIN Raden Intan Lampung, 2026)
This study analyzes the phenomenon of fragmented Islamic preaching content on social media as a new form of fragmentation of Islamic knowledge in the digital era. Using a qualitative approach with a digital case study design, this research focuses on viral content on TikTok, Instagram, and YouTube. Data were collected through digital observation (netrography), content analysis, and interviews with active users. The results show that the presentation of Islamic teachings in a concise and algorithmic format causes an epistemic discontinuity, a disconnect between classical sources and their delivery in the digital space. This fragmentation is not only informational but also epistemological, especially among the younger generation who tend to understand Islam through instant and emotional discourse. Social media algorithms act as epistemic actors that prioritize sensational content, create religious echo chambers, and shift religious authority from religious scholars to digital preachers. However, asocial media also has the potential to revitalize Islamic preaching if integrated with the principles of moderation, depth, and integrity. This study confirms that religious knowledge in the digital era is constructive, formed through the interaction of users, algorithms, and evolving digital narratives.